2022
DOI: 10.3389/fonc.2022.632042
|View full text |Cite|
|
Sign up to set email alerts
|

ASPM Is a Prognostic Biomarker and Correlates With Immune Infiltration in Kidney Renal Clear Cell Carcinoma and Liver Hepatocellular Carcinoma

Abstract: BackgroundAbnormal spindle microtubule assembly (ASPM) is a centrosomal protein and that is related to a poor clinical prognosis and recurrence. However, the relationship between ASPM expression, tumor immunity, and the prognosis of different cancers remains unclear.MethodsASPM expression and its influence on tumor prognosis were analyzed using the Tumor Immune Estimation Resource (TIMER), UALCAN, OncoLnc, and Gene Expression Profiling Interactive Analysis (GEPIA) databases. The relationship between ASPM expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Vincent et al demonstrated that ASPM was an essential regulator of Wnt-Diseveled-3-β-catenin signaling and cancer stemness in prostate cancer, which can promote prostate cancer cells proliferation [ 35 ]. Another study identified that ASPM increased levels of immune cell infiltration in KIRC and LIHC [ 36 ]. Notably, enrichment analysis showed that NCAPD2 was associated with the Wnt signaling, which perhaps indicated NCAPD2 and ASPM may promote the development of various tumors immunity via Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Vincent et al demonstrated that ASPM was an essential regulator of Wnt-Diseveled-3-β-catenin signaling and cancer stemness in prostate cancer, which can promote prostate cancer cells proliferation [ 35 ]. Another study identified that ASPM increased levels of immune cell infiltration in KIRC and LIHC [ 36 ]. Notably, enrichment analysis showed that NCAPD2 was associated with the Wnt signaling, which perhaps indicated NCAPD2 and ASPM may promote the development of various tumors immunity via Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…26 ASPM has also been shown to promote cancer progression. 27,28 TOP2A and CDNK3 have been screened to be involved in colorectal cancer progression. 29 Currently, TOP2 has been widely used in targeted therapy of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al identify 14 key genes related to the pathogenesis of colon cancer, including CEP55, TOP2A, RRM2, NCAPG2, providing new directions for elucidating the molecular mechanisms of colon cancer 26 . ASPM has also been shown to promote cancer progression 27,28 . TOP2A and CDNK3 have been screened to be involved in colorectal cancer progression 29 …”
Section: Discussionmentioning
confidence: 99%
“…ASPM, which is involved in mitotic spindle regulation and coordination of mitotic processes, has already been identified as a tumor marker in other settings. In an attempt to clarify the role of ASPM in tumor immunity and the prognosis of different cancers, Deng et al analyzed the expression of ASPM in different tissues including kidney renal clear cell carcinoma and liver hepatocellular carcinoma ( Deng et al, 2022 ). In these two types of cancers, higher expression of ASPM was evidenced in cancer tissues with respect to normal corresponding tissue, in late-stage cancers versus early-stage ones.…”
Section: Discussionmentioning
confidence: 99%